2010
DOI: 10.1111/j.1365-3032.2010.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bacterially‐dense environments on the development and immune defences of the blowflyLucilia sericata

Abstract: . (2011) AbstractCompetitive interactions between insects and microbes and the associated cost of development in bacterially-dense environments are investigated using the blowfly Lucilia sericata (Meigen) as a model. The effects of developing in a bacterially-dense environment are measured by assessing the fitness consequences of competition using the pathogen Staphylococcus aureus. Fitness is quantified in terms of larval survival, puparial development and adult emergence.The influence of bacteria on larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…In the house fly ( Musca domestica ), which has also been used in larval therapy [18], certain bacteria are associated with reduced growth and high mortality rates, while others promote larval development [19, 20]. In the blow fly L. sericata , which is typically used for wound debridement, available data about effects of bacteria on larval growth and survival are limited to a single bioassay with Staphylococcus aureus which did not find any effect of the bacterium on larval development [21]. However, it has been reported that certain bacteria affect immune responses of the maggots [22], so the potential effect of microorganisms on larval survival and development should not be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…In the house fly ( Musca domestica ), which has also been used in larval therapy [18], certain bacteria are associated with reduced growth and high mortality rates, while others promote larval development [19, 20]. In the blow fly L. sericata , which is typically used for wound debridement, available data about effects of bacteria on larval growth and survival are limited to a single bioassay with Staphylococcus aureus which did not find any effect of the bacterium on larval development [21]. However, it has been reported that certain bacteria affect immune responses of the maggots [22], so the potential effect of microorganisms on larval survival and development should not be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…aureus or reared in a sterile environment [26]. However, in terms of development rate, further work will need to be done to see if this species remains robust to a wider range of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Research to date demonstrates that, whilst ingesting the common skin bacterium S. aureus has no effect on pupation times, pupal size or survival rate of Lucilia sericata (Meigen) [26], certain bacterial strains have been shown to have a negative impact on blow fly larval development. For example, Ahmad et al [27] isolated four gut mutualistic bacteria (Providencia sp., Escherichia coli O157:H7, Enterococcus faecalis, and Ochrobactrum sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Both Staphylococcus aureus (a relatively ubiquitous gram-positive organism common to humansÕ skin and nasopharynx) and E. coli have been shown to be eaten and killed by L. sericata as well as by some nonnecrophagous ßies (Mumcuoglu et al 2001, Erickson et al 2004, Barnes and Gennard 2011. Although S. aureus can be found on decaying tissues and, therefore, may be consumed by larvae, its presence is not necessary for proper development, and high concentrations of the organism do not seem to inhibit larval development or survival.…”
Section: The Roles Of Microorganisms and Microbial Products In The Sumentioning
confidence: 99%